Pengaruh Kemudahan Dan Manfaat Intranet Dengan Mempertimbangkan Gender Terhadap Motivasi Penggunanya Di Bank BPD DIY - Sulthoni, Ikhwan (208-7721)
The purpose of this research is to analyze the influence of perceived ease of use and perceived usefulness considering the gender toward intention for using intranet in Bank BPD DIY with Technology Acceptance Model (TAM). The sample method is purpose sampling with the criteria are employees in Bank BPD DIY who are using intranet Bank BPD DIY to support job description. Multiple regression analysis was used to test the hypothesis. The result reveals that all of the independent variables they are perceived ease of use and perceived usefulness positively significant influence to intention to use intranet in Bank BPD DIY as the dependent variable. The gender did not moderate perceived ease of use and perceived usefulness toward intention for using intranet in Bank BPD DIY, so that employees both men and women have the same motivation in the implementation intranet to support the task in Bank BPD DIY